PSYCHOLOGICAL AND PSYCHOBIOLOGICAL FACTORS AS MEASURE OF INTEGRITY IN SOCCER PLAYERS - SAHA SRILEKHA; SAHA, SOUMENDRA (International Journal of Pharma and Bio Sciences, 2015)
Present study was conducted to observe the predictive association between differential mood states; emotional feelings and corroborative psychobiological changes with regard to inner core emotional reactions observed in high-performing soccer players of Malaysia. Based on the selection criteria altogether two-hundred and thirteen young male soccer players were recruited as participants, who were subjected to evaluation of projective analyses of emotionality (in the form of index of emotional integrity; impulsivity and irritability); mood states and inner psychobiological status (autonomic indices of habituation paradigm skin conductance response components). Multiple linear regression analyses outcomes however clarified relationships between the inner core of emotionality; differential mood variations and psychobiological indices of emotionality. The combined impact of Skin conductance indices and mood states revealed that those can explain differential etiological aspects of emotional integrity, while inclusion of emotional feelings of impulsivity and irritability were observed to predict stronger relationships. Innate psychological make-up of players was found substantially associated with autonomic orienting activity indices, which were evidentially capable of explaining cognitive-motivational aspects of soccer performance.